The psychological impacts of COVID-19 pandemic on nursing students - Phuekphan, Patra; Setchoduk, Kanyaphat; Saiklang, Parvinee (Thai Journal of Nursing, 2022)
During the COVID-19 pandemic, nursing students have variety of psychological impacts as follows. 1) Having negative emotions including feelings of shocked, confused, instability, uncertainty, anxiety, fear, stress, depression, feelings of loneliness, sadness and despair, burnout and fatigue, and social unsupport. 2) Having positive emotions including the excited feeling and pride. However, this COVID-19 pandemic does not affect their nursing career decision. In addition, the preventive measures and solutions of these psychological impacts including physical activity performance, changing the worldview, social preparedness and getting social support, are utilized in coping with the COVID-19 pandemic.